Mycelial growth, sporulation and spore germination of virulent Colletotrichum gloeosporiodes f. sp. manihotis isolates under selected growth conditions - Fokunang, C.N.; Ikotun, T.; Dixon, A. (1995)
Thirty isolates of Colletotrichum gloeosporioides f. sp. manihotis causal organism of cassava anthracnose disease (CAD), were collected from cankers on cassava stems in cassava-growing zones of Nigeria. Using a pathogenicity test, five virulent isolates (05FCN, 10FCN, 12FCN, 18FCN and 26FCN) were identified and subsequently used in determining the effect of temperature, pH, light and growth medium on mycelial growth, sporulation and spore germination.